PATH-13. INTRAOPERATIVE EVALUATION OF IDH MUTATION STATUS AND TUMOR INVASION IN GLIOMA. (12th November 2021) - Brown, Hannah; Garcia, Diogo; Chen, Rong; Jentoft, Mark; Middlebrooks, Erik; Chaichana, Kaisorn; Quinones-Hinojosa, Alfredo; Cooks, R Graham
Abstract: BACKGROUND: Intraoperative detection of residual tumor and isocitrate dehydrogenase (IDH) mutations can assist in maximizing surgical resection beyond contrast enhancing margins and guide intraoperative surgical decision making for glioma patients. We aimed to evaluate the use of desorption electrospray ionization-mass spectrometry (DESI-MS) for intraoperative assessment of IDH mutations and estimation of tumor cell percentage (TCP). METHODS: This is a prospective study using intraoperative DESI-MS analysis of freshly obtained tissue samples to evaluate IDH mutations via 2-hydroxyglutarate (2-HG) intensity and TCP via measurement of N-acetylaspartic acid (NAA) intensity and characteristic lipid profiles. These IDH mutation and TCP estimates were subsequently validated by a senior neuropathologist. RESULTS: A total of 247 biopsies from a 49-patient study were previously collected and analyzed at Indiana University. Assessment of TCP in 203 margin and core biopsies based on NAA intensity yielded sensitivity, specificity, and accuracy values of 91, 76, and 83%, whereas TCP assessment based on characteristic lipid profiles yielded 76, 85, and 81%, respectively. Assessment of IDH mutation status of 71 core biopsies yielded sensitivity, specificity, and accuracy values of 89, 100, and 94%. Further validation of the methodology is being performed in an ongoing collaboration with Mayo Clinic-Jacksonville, where we have collected 178 biopsies from 24 patients. Preliminary results of IDH mutation assessments indicate 100% sensitivity, specificity, and accuracy. DISCUSSION/CONCLUSION: We present a novel system to allow intraoperative evaluation of IDH status and to guide surgical resection by TCP measurement from tissue biopsies. Prospectively, we propose to modify our DESI-MS system by placing a surgical material (e.g. cottonoid) along the surgical margin and transferring material from the blot to a microscope slide prior to DESI-MS analysis. This will allow the retention of the spatial distribution of diagnostic molecules while analyzing a wall of the surgical cavity without the need for biopsy.